Environmental change during MIS4 and MIS 3 opened corridors in the Horn of Africa for Homo sapiens expansion. (15th December 2018) - Viehberg, Finn A.; Just, Janna; Dean, Jonathan R.; Wagner, Bernd; Franz, Sven Oliver; Klasen, Nicole; Kleinen, Thomas; Ludwig, Patrick; Asrat, Asfawossen; Lamb, Henry F.; Leng, Melanie J.; Rethemeyer, Janet; et al.
Abstract: Archaeological findings, numerical human dispersal models and genome analyses suggest several time windows in the past 200 kyr (thousands of years ago) when anatomically modern humans (AMH) dispersed out of Africa into the Levant and/or Arabia. From close to the key hominin site of Omo-Kibish, we provide near continuous proxy evidence for environmental changes in lake sediment cores from the Chew Bahir basin, south Ethiopia. The data show highly variable hydroclimate conditions from 116 to 66 kyr BP with rapid shifts from very wet to extreme aridity. The wet phases coincide with the timing of the North African Humid Periods during MIS5, as defined by Nile discharge records from the eastern Mediterranean. The subsequent record at Chew Bahir suggests stable regional hydrological setting between 58 and 32 kyr (MIS4 and 3), which facilitated the development of more habitable ecosystems, albeit in generally dry climatic conditions. This shift, from more to less variable hydroclimate, may help account for the timing of later dispersal events of AMH out of Africa. Highlights: Multiproxy record from S Ethiopia extends knowledge about environment and climate of past 116, 000 yrs during human expansion. Hydroclimate during Marine Isotope Stage (MIS) 5 was much more variable (frequency and amplitude) than during MIS 3 and 4. Earth system models and model simulations of intermediate complexity emulate corresponding amplitude shifts in hydroclimate. Environment was arid during MIS 3 and 4, but permanent lake water bodies existed as inferred from our biological proxies.